De novo transcriptome analysis and highly sensitive digital gene expression profiling of Calliphora vicina (Diptera: Calliphoridae) pupae using MACE (Massive Analysis of cDNA Ends). (March 2015) - Zajac, B.K.; Amendt, J.; Horres, R.; Verhoff, M.A.; Zehner, R.
Highlights: We analyzed the transcriptome of pupae of the blow fly Calliphora vicina . MACE provided high-resolution gene expression profiles of 15 pupal development stages. 53, 539 distinct transcripts were detected, 7548 (14.1%) were annotated to known genes. Genes of Interest (GOI) for each of the 15 pupal stages were identified and support molecular age estimation in forensic entomology. Abstract: Determining a post-mortem interval using the weight or length of blow fly larvae to calculate the insect's age is well established. However, to date, there are only a handful studies dealing with age estimation of blow fly pupae, in which weight or length cannot be used as a relevant parameter. The analysis of genetic markers, which indicate a certain developmental stage, can extend the period for a successful post-mortem interval determination. In order to break new ground in the field of age determination of forensic relevant blow flies, we performed a de novo transcriptome analysis of Calliphora vicina pupae at 15 different developmental stages. Obtained data serve as base to establish molecular age determination techniques. We used a new, deeper, and more cost-effective digital gene expression profiling method called MACE (Massive Analysis of cDNA Ends). We generated 15 libraries out of 15 developmental stages, with 3–8 million reads per library. In total, 53, 539 distinct transcripts were detected, and 7548 were annotated to known insect genes. The analysis provides high-resolution gene expression profiles of all covered transcripts, which were used to identify differentially expressed genetic markers as candidates for a molecular age estimation of C. vicina pupae. Moreover, the analysis allows insights into gene activity of pupal development and the relationship between different genes interesting for insect development in general.